Donated fortified cereal blends improve the nutrient density of traditional complementary foods in Haiti but iron and zinc gaps remain for infants - Ruel, Marie T.; Menon, Purnima; Loechl, Cornelia U.; Pelto, Gretel H. (SAGE Publications, 2004)
This research assesses whether fortified cereal blends such as corn-soy blend (CSB) or wheat-soy (WSB) blend can significantly contribute to improving the quality of the diet of infants and young children 6 to 23 months of age. A series of participatory recipe trials was conducted to assess current complementary feeding practices in the Central Plateau of Haiti and to develop new, improved recipes by using a combination of locally available ingredients and foods and donated fortified cereal blends. Our findings show that it is feasible to improve the nutritional quality of complementary foods in poor rural areas of Haiti, using locally available ingredients and fortified cereal blends. Significant improvements in the concentrations of vitamin A could be obtained by including acceptable and affordable amounts of locally available vitamin A-rich foods such as pumpkin or eggs. Only preparations using CSB, however, could achieve the recommended concentrations of iron and zinc in complementary foods, and even this was achievable only for 12- to 23-month-old children. For infants, and especially those between 6 and 8 months of age, the high requirements of 7.7 mg of iron and 1.6 mg of zinc per 100 kcal of complementary foods could not be met, even with a combination of fortified CSB and other locally available, acceptable, and affordable foods. The same was true for the zinc density of complementary foods among 9- to 11-month-old children, which could not be achieved even with fortified CSB. Thus, in this population, fortified cereal blends were key to achieving the recommended iron and zinc densities of complementary foods for children 12 to 23 months of age, but they were not sufficient for infants. Complementary approaches, such as improving the availability, access, and intake of animal-source foods or the use of home fortification techniques (using spreads, sprinkles, or dispersible tablets), are needed to ensure adequate iron and zinc density of complementary foods for infants younger than 12 months in resource-constrained environments such as rural Haiti.